CONVERGENCE OF IT AND BUSINESS IN CONNECTED ECONOMY AS A DRIVER FOR ORGANIZATIONS' DIGITAL TRANSFORMATION - SIBORA ROSANNA (2017)
This article discusses the importance of digital transformation and cross-departmental collaboration between IT and business units in the age of connected economy. The aim of the article is to highlight the most crucial aspects of IT-business relationship, contributing to the successful realization of organization’s transformation process. The author also provides a roadmap for how companies might undergo a digital transformation. Well designed and executed digital transformation roadmap will contribute to the establishment of solid IT-business relationship and IT’s strategic role within the company, as well as – above all – to the digital-driven value creation process and in this way to company’s competitive advantage.